Prospects for mapping temporal height variations of the seasonal CO2 snow/ice caps at the Martian poles by co-registration of MOLA profiles - Xiao, Haifeng; Stark, Alexander; Steinbrügge, Gregor; Thor, Robin; Schmidt, Frédéric; Oberst, Jürgen (Planetary and Space Science, 2022)
We investigate the feasibility and demonstrate the merits of using Mars Orbiter Laser Altimeter (MOLA) profiles to retrieve seasonal height variations of CO2 snow/ice cap in Mars’ polar areas by applying a co-registration strategy. We present a prototype analysis on the research region of [85.75°S, 86.25°S, 300°E, 330°E] that is located on the residual south polar cap. Our method comprises the recomputation of MOLA footprint coordinates with an updated Mars Global Surveyor (MGS) ephemeris and a revised Mars rotation model. The reprocessed MOLA dataset at the South Pole of Mars (poleward of 78°S) is then self-registered to form a coherent reference digital terrain model (DTM). We co-register segments of reprocessed MOLA profiles to the self-registered MOLA reference DTM to obtain the temporal height differences at either footprints or cross-overs. Subsequently, a two-step Regional Pseudo Cross-over Adjustment (RPCA) procedure is proposed and applied to post-correct the aforementioned temporal height differences for a temporal systematic bias and other residual errors. These pseudo cross-overs are formed by profile pairs that do not necessarily intersect, but are connected through the underlying DTM. Finally, CO2 snow/ice temporal height variation is obtained by median-filtering those post-corrected temporal height differences. The precision of the derived height change time series is ∼4.7 cm. The peak-to-peak height variation is estimated to be ∼2 m. In addition, a pronounced ”pit” (transient height accumulation) of ∼0.5 m in magnitude centered at Ls = 210° in southern spring is observed. The proposed method opens the possibility to map the seasonal CO2 snow/ice height variations at the entire North and South polar regions of Mars.